2022
DOI: 10.1177/13674935221136229
|View full text |Cite
|
Sign up to set email alerts
|

‘Diagnosis, disclosure and stigma: The perspectives of Indonesian children with HIV and their families’

Abstract: This grounded theory study aimed to explore the subjective experiences of children living with Human Immunodeficiency Virus (HIV) from the perspective of children and their families in Indonesia. Twenty participants were interviewed, consisting of 12 children aged 9–18 years and eight family members. Using grounded theory analysis, this study identified three categories: ‘coping with diagnosis’, ‘disclosing their status’ and ‘living with the stigma of HIV’. Participants responded with shock, denial, sadness, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…Many studies have found that AYA living with HIV can face negative consequences due to others finding out about their status including that of being socially rejected and isolated. [59][60][61] Both perceived and experienced social rejection are common occurrences that AYA living with HIV face. 59,62 Perceived social rejection itself perpetuates AYA living with HIV being advised to and actively choosing not to disclose their status.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that AYA living with HIV can face negative consequences due to others finding out about their status including that of being socially rejected and isolated. [59][60][61] Both perceived and experienced social rejection are common occurrences that AYA living with HIV face. 59,62 Perceived social rejection itself perpetuates AYA living with HIV being advised to and actively choosing not to disclose their status.…”
Section: Discussionmentioning
confidence: 99%
“…Cuidadores de crianças soropositivas evitam revelar o diagnóstico de infecção pelo HIV, buscando protegê-las das consequências emocionais e sociais de serem portadores de uma enfermidade grave, crônica e estigmatizante (Programa Estadual DST/Aids-SP, 2008) e, portanto, muitas vezes necessitam de ajuda profissional para conseguirem revelar o diagnóstico a estas crianças (Joyce et al, 2022;Qur'aniati et al, 2022), de forma a favorecer a adesão ao tratamento e a compreensão de sua realidade, porém sem gerar traumas e revoltas. A revelação do diagnóstico deve ser feita, o mais breve possível, em conjunto com os cuidadores, em um processo contínuo, comunicando às crianças que vivem com o HIV informações claras e precisas (Ministério da Saúde, 2009).…”
Section: Discussionunclassified
“…O esclarecimento diagnóstico às crianças soropositivas que adquiriram o vírus por transmissão vertical (quando a infecção é transmitida da mãe biológica para o bebê durante o período de gestação, parto ou aleitamento) é um dos aspectos que causa maiores dificuldades psicológicas de enfrentamento para as famílias. Os principais motivos para os pais e cuidadores adiarem esta revelação e manterem segredo sobre o diagnóstico são: o medo da criança não conseguir guardar segredo sobre sua condição de saúde e vivenciar situações de discriminação, preconceito e isolamento social; a exposição da história familiar e da forma de contágio pelo vírus; o receio de que a criança desenvolva sentimentos de culpabilização, raiva e revolta em relação aos pais (Barfield & Kane, 2008;Bhattacharya et al, 2011;Castellani & Moretto, 2016;Joyce et al, 2022;Kouyoumdjian et al, 2005;Marques et al, 2006;Ministério da Saúde, 2018;Negrini, 2017, Programa Estadual DST/Aids-SP, 2008Qur'aniati et al, 2022;Silveira, 2008). O estigma que leva a situações de preconceito é decorrente da associação que ainda se faz na sociedade entre comportamentos de risco e HIV/aids, culpabilizando o indivíduo pela infecção, inferindo uso de drogas e promiscuidade (Maman et al, 2009;Simbayi et al, 2007).…”
Section: Introductionunclassified